Pelatihan Pengaturan Sarapan Pagi pada Anak Sekolah di SDN Salakan I Potorono Banguntapan Bantul - Sri Sularsih Endartiwi (Humanism: Journal of Community Empowerment (HJCE), 2019)
ABSTRACTSalakan Government Elementary School I is one of the primary schools in BanguntapanDistrict, Bantul Regency. In the school based on information from the principal that 45% of theirstudents are not used to breakfast. This condition is caused by parents who do not serve breakfast,children do not want to eat breakfast even though their parents have prepared breakfast, there arealso children who do not like breakfast because they are afraid of arriving late at school. Studentscan find out about breakfast and food that can be used for breakfast. Students are also expected tobe able to prepare food for breakfast. Used metode Counseling and training. Knowledge of SalakanGovernment Elementary School I Potorono students has increased knowledge after counseling andtraining on breakfast from 40% to 95%. Students can practice preparing a healthy and nutritiousbreakfast. Can conclusing Students' knowledge about breakfast improved after counseling andtraining.Keywords: breakfast, students